ANALISIS PERTUMBUHAN DAN KELULUSHIDUPAN LARVA LELE (Clarias gariepenus) YANG DIBERI PAKAN Daphnia SP. HASIL KULTUR MASSAL MENGGUNAKAN PUPUK ORGANIK DIFERMENTASI - Merawati VE; Muhamad Agus (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
This  research  was  done  for  analyzing  the  influence  of  the  Daphnia  which  is  cultured  by organic fertilizer like, chicken  dung,  rice  shifting,  bungkil (residue  of copra  after  extracting oil) which were fermented prebiotic bacteria toward the growth and survival ratio of cat fish larva.... the threatment are (A) chicken dung 1.2 g/l of, rice shifting 1.2 g/l, (B) chicken dung 1.2 g/l of, bungkil 1.2 g/l, (C) chicken dung 1.2 g/l of, rice shifting 0.3 g/l, and bungkil 0.9 g/l, (D) chicken dung 1.2 g/l of, rice shifting 0.9 g/l, and bungkil 0.3 g/l, (E) chicken dung 1.2 g/l of, rice shifting 0.6 g/l, and bungkil 0.6 g/l,   (F)  Non-fermented  Chicken  dung  2,4  g/l. Three  days  of  cat  fish  larva  was  spread  in  a  100x50x40  cm  aquarium  with  48  fish/  liter stockdensity. The Daphnia feeding was given in five times a day in adlibitum during 14 days. The result of the relative growth showed the real distinguish (p>0,05) with the best growth on treathment B. Survival ratio showed that there was no difference (p<0,05).  Key word : organic fertilizer like, fermentation, cath fish of larva, growth, survival ratio.